ANALISIS KONFLIK BATIN TOKOH UTAMA DALAM NOVEL DD: ELEGI SEORANG PENYANYI DANGDUT KARYA RONIERAYS - Savitri, Dewi (Humanis; Volume 5. No. 2. November 2013, 2014)
Artikel This article analyzes the inner conflict of the main character in the novel DD: An Elegy dangdut singer Ronierays work. The reason this article the authors made is to have a psychological picture that stands out, especially the main character is named Pricilla, a woman who described experiencing inner conflict continuously, so the women find happiness (cheating) outside the true happiness that has obtained. In the novel DD: An Elegy dangdut singer, the female figures depicted on the nature, thinking, and behavior. All thing are illustrated clearly, it can be understood for another woman heart who seeking the happiness. To find out how exactly the picture of mental Prisyla figures, and description of how nature, thought patterns, and feelings that make up personal Prisyla figures, then analyzed by psychology as a science aid. Prisyla is a very selfish woman, in order to achieve happiness he was willing to leave his family. The theory used in this article there are two kinds of psychological theories of structuralism and literary theory. Furthermore inner conflicts figures also uses the theory of psychoanalysis. Psychological aspects described in the three elements of Sigmund Freud's personality, such as Id, Ego, and Superego. Conflict is a picture of mental instability which then forms the climax of the conflict pattern.
Keywords: Psychology, Inner Conflict, and DD Novel: An Elegy dangdut singer